China's carbon capture, utilization and storage (CCUS) policy: A critical review. (March 2020) - Jiang, Kai; Ashworth, Peta; Zhang, Shiyi; Liang, Xi; Sun, Yan; Angus, Daniel
Abstract: Carbon capture, utilization and storage (CCUS), has been deemed an essential component for climate change mitigation and is conducive to enabling a low-carbon and sustainable future. Since the 12th Five-year Plan, China has included this technology as part of its future national carbon mitigation strategies. China's policy framework in relation to CCUS has had a strong influencing role in the technology's progress to date. This paper employs the "policy cycle" to analyze China's existing CCUS regulatory framework at the national and provincial level, evaluate its performance and clarify its shortcomings in light of the comparisons of policy movements undertaken in other countries. The results indicate that China's CCUS policy is insufficient for further development of the technology and many issues remain to be solved. This includes the lack of an enforceable legal framework, insufficient information for the operationalization of projects, weak market stimulus, and a lack of financial subsidies. These factors may be the reason we have seen low participation rates of Chinese companies in CCUS and little public understanding of what the technology offers. To overcome these challenges, suggestions are provided for improving China's CCUS legal and policy framework. Highlights: The development of China's CCUS policy framework is reviewed. China's national Five-year Plans referring to CCUS affect provincial policies as they share similar objectives since 2011. China's national policies influence China's research and engineering practices related to CCUS. China's CCUS fails to meet the proposed targets in technology roadmap issued during the period of the 12 th Five-year Plan. Recommendations to amend the regulatory framework for CCUS in China are provided.